Evaluation of the protection of astaxanthin on human hair follicle palilla cells against the aging effects triggered by hydrogen peroxide - Thu, Nguyen Thi Mong; Quynh, Nguyen Phan Nhu; Van, Dang Nguyen Tuong; Uyen, Luu Tran Thanh; Hoang, Ho Thien; Long, Le Thanh; Chi, Ho Nguyen Quynh; Quan, To Minh (Vietnam Journal of Biotechnology, 2024)
Astaxanthin (ASX) is a powerful antioxidant with high efficacy in inhibiting reactive oxygen species (ROS), one of the most harmful factors leading to hair loss. Our research specifically evaluated the ability of ASX to protect human dermal papillae cells from hydrogen peroxide (H2O2). In this study, the human dermal papillae (hDP) cells were successfully isolated. The cells expressed DP cell markers in the 2D model, including alkaline phosphatase, alpha-smooth muscle actin (98.66 ± 0.02%), and vimentin (98.88 ± 0.02%), cluster aggregation and spheroid formation in the 3D model. The hDP cells (P3-P5) were pretreated with ASX and subsequently treated with H2O2 at a concentration of 550 µM for 4 hours. After 4 days of treatment, the percentage of cells expressing the marker b-galactosidase decreased from 87 ± 0.01% in the control group to 27.61 ± 0.01% in the ASX-treated group (1 µg/mL). Our results indicated that astaxanthin effectively protects against oxidative stress in dermal papillae cells, suggesting its potential application in hair loss treatment due to ROS.